Determinants of Exclusive Breastfeeding Practice in Gorontalo Province - Dio Dwi Saputra (Internasional Journal of Data Science, Engineering, and Anaylitics, 2022)
Exclusive breastfeeding has many benefits, not only for the baby but also for the mother. In 2021, the province with the lowest percentage of babies aged 0-5 months old who received exclusive breastfeeding in Indonesia is Gorontalo Province (52,75 percent). This makes the background of the researcher to find out the determinants of exclusive breastfeeding practice in this province. this study uses a dataset from the National Socio-Economic Survey (SUSENAS) in Gorontalo Province in March 2021. The variables used are age at first marriage, maternal education, internet usage, place of birth, assistant of birth, and household poverty status. The result is that women aged 15-49 years whose first marriage age is 21 years and over (OR = 0,77), with junior high school and over education (OR = 0,93), used the internet for the past 3 months (OR = 0,77) and their household poverty status is not poor (OR = 0,86) tend not to practice the exclusive breastfeeding. While women aged 15-49 years who gave birth at home are more likely to practice exclusive breastfeeding (OR = 1,95).